Strategy and leadership as service : how the access economy meets the c-suite - Daw, Sara (New York : Routledge, 2024)
"Strategy and Leadership as Service isn't just a nice idea; it is a practical, alternative vision of the future of work for senior executives that is starting to gain significant interest and is being adopted by businesses globally. Disrupting and challenging the traditional full-time employment model, the Strategy and Leadership as Service framework provides businesses with access to the complete range of functional, emotional, and collective intelligence at the C-Suite level by moving their positions from the "pay-roll" to an "access-role." Many entrepreneurial and growing businesses don't need, don't want, and can't afford full-time C-suite executives. For larger organisations, it is becoming harder to find the skills and knowledge required to fulfil all the obligations of a functional C-suite with a fixed group of individuals. By moving to the Strategy and Leadership as Service framework, the outcomes are better for all stakeholders: more engagement, access to the right skillsets and mindsets at the right time and in the right quantity to match the changing business agenda, more flexibility for senior leaders, and strengthened risk management. Through presenting a working business model, and real-world case studies throughout, this book provides executives and leaders with a complete understanding of this ground-breaking approach and its key benefits, the theory upon which it is based, its essential ingredients, the mindset change required and, most importantly, how to apply it in practice. The book provides business leaders, C-suite portfolio executives, human resource professionals, strategy consultants, leadership coaches, organisational development consultants, recruiters, professional service firms, academics, and forward-thinking business students with a radical new view of how the access economy can be applied to business strategy and leadership for more sustainable futures"--
Keywords: Leadership; Executives; BUSINESS & ECONOMICS / Human Resources & Personnel Management